2022
DOI: 10.3389/fpubh.2022.1072137
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine response and safety in patients with cancer: An overview of systematic reviews

Abstract: BackgroundTo date, the COVID-19 pandemic does not appear to be overcome with new variants continuously emerging. The vaccination against COVID-19 has been the trend, but there are multiple systematic reviews on COVID-19 vaccines in patients with cancer, resulting in redundant and sub-optimal systematic reviews. There are still some doubts about efficacy and safety of the COVID-19 vaccine in cancer patients.PurposeTo identify, summarize and synthesize the available evidence of systematic reviews on response and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Patients with cancer are recommended for boosters as well. 8 After the second dose, there is still disagreement on the vaccine's efficacy. A fourth dose is advised because the already-established immunity is still underwhelming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with cancer are recommended for boosters as well. 8 After the second dose, there is still disagreement on the vaccine's efficacy. A fourth dose is advised because the already-established immunity is still underwhelming.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of cancer cases to establish immunity against severe acute respiratory syndrome coronavirus 2 has been found to be enhanced by receiving a third dosage of the vaccine, according the current study. 8 Consideration should be given to the mRNA vaccine, which among a variety of vaccine types has the best immunogenicity. The booster immunization using the mRNA vaccine should be helpful in terms of preventive oncology given the current state of the outbreak and the future guidelines on immunizing a patient with an underlying cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews including a great number of studies have already shown that COVID-19 vaccines are effective and safe in patients with chronic diseases, such as malignancies, immune-mediated inflammatory disease, and immunocompromised patients. 59 Moreover, evidence from studies including individuals with cardiovascular disease supports the safety and effectiveness of COVID-19 vaccines in this population group. 10,11 That is, the Heart Failure Association of the European Society of Cardiology and the American Heart Association suggest COVID-19 vaccination as soon as possible to individuals with heart failure, heart disease, heart attack, and cardiovascular risk factors since they are high risk groups to develop COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…for whom vaccination was available as of June 2021. Specifically, patients in Colombia have had access to different alternatives: the chemically inactivated vaccine, CoronaVac, designed to be administered in two doses and with a seroconversion rate greater than 90% 9 ; Two vaccines with viral vector technology, ChAdOx1 nCoV-19, with a two-dose schedule and reported efficacy between 62 and 90% 10 ; Ad26.COV2.S, proposed for an initial one-dose schedule, with a reported percentage of seroconversion from 80 to 100% 8 ; And finally, two vaccines with nucleic acid technology encoding a protein antigen, BNT162b2 12 , 13 , and mRNA-1273 14 , 15 , both to be administered initially in two-dose regimens and with reported seroconversion percentages of 100%.…”
Section: Introductionmentioning
confidence: 99%